Research on China’s New Energy Cross-Provincial Marketization Mechanism Under the Background of “Double Carbon” - Zhou, Qiang; Li, Jin; Lv, Qingquan; Wang, Dingmei; Yang, Shiyou (Frontiers in Energy Research, 2022)
In the past decade, China’s new energy has experienced a prosperous development and has become an important main power supply in China. With the promotion of China’s power market–oriented reform, the market-oriented transaction mechanism will play an essential role for China to achieve a large-scale and efficient national allocation of new energy. This study systematically analyzes and designs the principle of China’s new energy cross-provincial marketization mechanism, including those for a compound system such as an interprovincial medium and long-term transaction and spot transaction. The proposed mechanism is validated by its implemental results on a prototype power system with new energy.